Justification of pathogenetic mechanisms of ungulomycosis in cows - N. M. Khomyn; V. V. Pritsak; I. I. Ihlitskyi (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The article presents the results of biochemical, biophysical, and histomorphological studies of the hoof horn of clinically healthy cows and patients with purulent pododermatitis complicated by keratomycetes. It is known that the development of the inflammatory process in the area of the hooves, in particular, due to purulent inflammation of the producing layer of the base of the skin, complicated by keratomycetes, affects not only the animal body as a whole but also the quality of the hoof horn, which is characterized by changes in its individual biochemical and biophysical indicators and the structure of the epidermis of the hooves. In particular, in the hoof horn of animals with ungulomycosis, there is a probable increase of 35.6 % in the concentration of SH-groups and 16.1 % in the moisture content, which indicates the deterioration of the keratinization process and, as a result, the accumulation of excessive moisture content in the epidermis of the hooves. It indicates a deterioration in the quality of the hoof horn. It has been established that the condition of the hoof horn is influenced by other biochemical indicators, in particular, the concentration of Sulfur and Calcium in the epidermis of the hoof. Thus, with ungulomycosis, the content of Sulfur decreases by 19.2 %, and calcium decreases by 13.9 %, which indicates the deterioration of keratinization processes.  Trace elements, particularly copper and zinc, also play an important role in this process. Purulent inflammation of the producing layer of the base of the skin of the hoofs, complicated by keratomicetes, decreases the concentration of these mineral substances by 18.1 and 16.2 %, respectively. Changes in the biochemical indicators of the epidermis of the cow's hooves due to ungulomycosis also affected its biophysical properties. Thus, hoof horn density decreased by 7.4 % and hardness by 17.8 %. It was established that in the presence of dystrophic and inflammatory processes at the base of the skin of the hooves, there are certain violations of the tissue (tubular) and cellular structure due to ungulomycosis. The horn of such hooves undergoes parakeratotic changes; loosening of fibers and destruction of cellular elements is observed. Thus, purulent pododermatitis of fungal origin is accompanied by changes in specific biochemical and biophysical parameters of the hoof horn, as well as histomorphological changes. These changes lead to irreversible processes in the epidermis of the hoofs and are one reason for the transition of the inflammatory process to deeper tissues and the involvement of the entire cow's hoof in this process.